Is there a “European Paediatrics”? - Dornbusch, Hans Jürgen; Kurz, Ronald; del Torso, Stefano; Hadjipanayis, Adamos; Tenore, Alfred (Frontiers in Pediatrics, 2024)
The journey from birth to adulthood is paved with threats to health and wellbeing, rendering this age group with its invaluable future potential particularly vulnerable. Therefore, children and adolescents deserve medical attention of the highest professional level based on solid, well founded training guidelines, the availability of a well-coordinated platform for the continuous acquisition of knowledge, exchange of ideas, and collaboration on research and clinical projects, and comprehensive continuing education. For the European region these crucial specifications are met to varying degrees by three major paediatric organisations: the European Academy of Paediatrics (EAP) with the European Board of Paediatrics (EBP) as the paediatric section of the European Union of Medical Specialists (UEMS PS), the European Paediatric Association (EPA/UNEPSA) and the European Confederation of Primary Care Paediatricians (ECPCP). A major goal of this paper is to call for the closest possible collaboration between these organizations in advocating for the health and rights of European children and adolescents and in effectively fostering the paediatric profession with a strong, unified voice.